Nebulized Hybrid Nanoarchaeosomes: Anti-Inflammatory Activity, Anti-Microbial Activity and Cytotoxicity on A549 Cells - Guerin Stabile, Sofia Giuliana (2025)
The properties of two hybrid nanoarchaeosomes (hybrid nanoARCs) made of archaeolipids extracted from the halophilic archaea Halorubrum tebenquichense and combining the properties of archaeolipid bilayers with metallic nanoparticles are explored here. BS-nanoARC, consisting of a nanoARC loaded with yerba mate (Ilex paraguariensis) extract (YME)-biogenic silver nanoparticles (BSs), and [BS + BS-nanoARC], consistent of a BS-nanoARC core covered by an outer shell of BSs, were structurally characterized and their therapeutic activities screened. By employing 109 ± 5 µg gallic acid equivalents (GAEs) and 73.4 µg chlorogenic acid/ YME mg as a silver reductive agent, spherical, heterogeneously sized (~80 nm diameter), −27 mV ζ potential, 90% Ag0 and λmax 420 nm BSs were obtained. We further prepared ~100–200 nm diameter, −57 mV ζ potential BS-nanoARC and ~300 nm diameter, −37 mV ζ potential [BS + BS-nanoARCs]. Freshly prepared and nebulized BS-nanoARCs reduced the release of TNF-α, IL-6 and IL-8 by LPS-irritated THP-1-macrophages and were highly anti-planktonic against S. aureus (MIC90: 13 ± 0.8 µg Ag/mL). While the nanoARCs and BS-nanoARCs were innocuous, freshly prepared [BS + BS-nanoARCs] magnified the cytotoxicity of BSs (IC50 12 µg Ag/mL vs. IC50 ~36 µg Ag/mL) on A549 cells. Such cytotoxicity remained after 30 days in the dark at 4 °C, while that of BSs was lost. Freshly prepared BSs also lost activity upon nebulization, whereas freshly prepared [BS + BS-nanoARCs] did not. However, the cytotoxicity of the [BS + BS-nanoARCs] was also lost when nebulized after 30 days of storage. Despite the harmful effects of storage and mechanical stress on the structure of the more active [BS + BS-nanoARCs], hybrid nanoARCs are promising examples of nanomedicines combining the properties of archaeolipids with antimicrobial silver nanoparticles and anti-inflammatory polyphenols that could complement oncologic therapies, reducing the usage of classical antitumoral agents, corticosteroids, and, importantly, of antibiotics, as well as their waste.